PERANAN KEPEMIMPINAN KEPALA DESA TERHADAP PENYELESAIAN KONFLIK SENGKETA TANAH DI DESA CEMBA KECAMATAN ENREKANG - Irfan Nopandi Ismail; Muhammad Rais Rahmat Razak (PRAJA: Jurnal Ilmiah Pemerintahan, 2020)
Abstract The purpose of this study was to determine the role of the village head's leadership in resolving the tana dispute conflict in Cemba village, Kec. Enrekang, Enrekang district. The type and type of this study used descriptive quantitative, the population in this study were all Cemba villagers as many as 1,875 people, and the sample of this study was 95 people. Data collection techniques carried out in this study were using techniques (1) observation, (2) questionnaires, (3) literature study. The collected data were then analyzed using frequency tables using a Likert scale and with the help of SPSS.The results of this study indicate that the leadership role of the Village Head in Cemba Village is 48.4% or categorized as Good enough, the way the land dispute conflict resolution in Cemba Village is 44.34% or categorized as Good enough, and based on research results can be concluded from the summary table results that there is a significant influence between the role of leadership of the Village Chief in resolving land dispute conflicts of 49.7% or categorized as Good enough.